2022
DOI: 10.1101/2022.06.20.496911
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nutrient and moisture limitation reveal keystone metabolites that link switchgrass rhizosphere metabolome and microbiome dynamics

Abstract: Plants exude large quantities of rhizosphere metabolites that can modulate composition and activity of microbial communities in response to environmental stress. While rhizodeposition dynamics have been associated with rhizosphere microbiome succession, and may be particularly impactful in stressful conditions, specific evidence of these connections has rarely been documented. Here, we grew the bioenergy crop switchgrass (Panicum virgatum) in a marginal soil, under nutrient limited, moisture limited, +nitrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 134 publications
(186 reference statements)
3
12
0
Order By: Relevance
“…Another paper showed that the root exudation of p -coumaric acid in rice increased by 1.95-fold in iN-than iN+ conditions ( 21 ). Therefore, our results from B. distachyon combined with the previous result suggest conserved patterns of increased production of compounds from the shikimate-phenylpropanoid pathway in root exudates of grasses under N-deficiency ( 20, 21 ).…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Another paper showed that the root exudation of p -coumaric acid in rice increased by 1.95-fold in iN-than iN+ conditions ( 21 ). Therefore, our results from B. distachyon combined with the previous result suggest conserved patterns of increased production of compounds from the shikimate-phenylpropanoid pathway in root exudates of grasses under N-deficiency ( 20, 21 ).…”
Section: Discussionsupporting
confidence: 80%
“…4A and B ). Similarly, switchgrass showed an increased amino acid exudation pattern under +N and +NP fertilization relative to unfertilized controls ( 20 ). Additionally, axenically grown maize under N deficiency lowered the amino acid amounts in root exudates ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations